Agricultural anaerobic digestion power plants in Ireland and Germany: policy and practice. (28th September 2016) - Auer, Agathe; Vande Burgt, Nathan H; Abram, Florence; Barry, Gerald; Fenton, Owen; Markey, Bryan K; Nolan, Stephen; Richards, Karl; Bolton, Declan; De Waal, Theo; Gordon, Stephen V; O'Flaherty, Vincent; et al.
Abstract: The process of anaerobic digestion (AD) is valued as a carbon‐neutral energy source, while simultaneously treating organic waste, making it safer for disposal or use as a fertilizer on agricultural land. The AD process in many European nations, such as Germany, has grown from use of small, localized digesters to the operation of large‐scale treatment facilities, which contribute significantly to national renewable energy quotas. However, these large AD plants are costly to run and demand intensive farming of energy crops for feedstock. Current policy in Germany has transitioned to support funding for smaller digesters, while also limiting the use of energy crops. AD within Ireland, as a new technology, is affected by ambiguous governmental policies concerning waste and energy. A clear governmental strategy supporting on‐site AD processing of agricultural waste will significantly reduce Ireland's carbon footprint, improve the safety and bioavailability of agricultural waste, and provide an indigenous renewable energy source. © 2016 Society of Chemical Industry